BRAINSTORMING, ACTIVATING, REINFORCING, APPLYING (BARA) AS A LEARNING STRATEGY IN LISTENING COMPREHENSION CLASSROOM - Ida Bagus Nyoman Mantra; Nengah Dwi Handayani; Dewa Gede Agung Gana Kumara; Ni Luh Putu Sapna Sagita; Ni Putu Dian Adnyani Putri (Journal on Studies in English Language Teaching (JOSELT), 2022)
Listening comprehension is an important language skill that needs to be developed continuously and intensively to enhance the student's language competence. This study used a classroom action research design conducted in two cycles of learning activities to improve students' listening comprehension through the BARA learning strategy. Indonesian educators developed the BARA learning strategy consisting of four learning stages: brainstorming, activating, reinforcing, and applying. This trial of the BARA strategy in an EFL classroom established the final construction of the BARA learning strategy. Data collection was done by administering a pretest, posttests and a questionnaire. The results showed that the student's listening comprehension improved significantly in the first and second learning cycles compared to the pretest result. Therefore, the BARA strategy is very effective in teaching listening comprehension. This study suggests that teachers should consider using the BARA learning strategy to improve students' language competence.